This I Believe - Kenton, Stan (Tufts Archival Research Center, 2006)
Stan Kenton is concerned with the development of humanity and he describes the need for growth and change for positive development to progress in all aspects of a person's life and also explains that everyone participates and contributes something to the development of humanity and his contributions and own developments are through music. This essay also contains an advertisement for a This I Believe LP album.